1996
DOI: 10.1111/j.1095-8649.1996.tb06072.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary stock assessment of the Patagonian toothfish longline fishery around the Falkland Islands

Abstract: An experimental fishery for Patagonian toothfish Di,ssosfichus rlcginoides was opened in Falkland Island waters briefly in 1992 and then from April 1994. One to two longlines per vessel were usually deployed at night, mostly fishing for 12-30 h at depths between 600 and 2000 m. The characteristics of the vessel, gear, fishing activities and the data collection and analyses methods are described. An initial evaluation of the authors' current understanding of toothfish biology and population dynamics in Falkland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
2
12
1
Order By: Relevance
“…Few tagging studies have been carried out, but fish are known to move within the Kerguelen Plateau, and there may be local movements around the Falkland Islands (Des Clers et al, 1996). One long distance migrant was reported with a fish tagged off the Falkland Islands recaptured several …”
Section: Discussionmentioning
confidence: 99%
“…Few tagging studies have been carried out, but fish are known to move within the Kerguelen Plateau, and there may be local movements around the Falkland Islands (Des Clers et al, 1996). One long distance migrant was reported with a fish tagged off the Falkland Islands recaptured several …”
Section: Discussionmentioning
confidence: 99%
“…The authors found that in two time series longer than 30 weeks, catch rates increased dramatically after a period of steady decline which was used in the assessment, apparently contradicting the authors' assumption of a closed population in DeLury model. Eventually, it was concluded that the results of the investigation are encouraging but cannot be generalised, and a better understanding of toothfish migrations is needed to provide a sound basis for the fishery's management (des Clers et al, 1996). Since then little information about stock status and its changes during the last 10 years of fishery is available.…”
Section: Introductionmentioning
confidence: 94%
“…Reproduction of the Falkland population happens on the eastern slope of Burdwood bank and immature fish forage over the eastern Patagonian shelf edge and slope (Laptikhovsky et al, 2004, in press). An attempt to assess the Falkland Islands toothfish population using a DeLury depletion method for some localised areas was made by des Clers et al (1996). The authors found that in two time series longer than 30 weeks, catch rates increased dramatically after a period of steady decline which was used in the assessment, apparently contradicting the authors' assumption of a closed population in DeLury model.…”
Section: Introductionmentioning
confidence: 96%
“…Many fish species found around the Falklands are shared stocks between Argentina and the Falkland Islands (Agnew, 2002). A clue to the apparent independence of toothfish in Falkland Island waters is given by the tendency of the species not to move very much as adults (Marlow et al, 2003;Williams et al, 2002), and the fact that two spawning and nursery areas are known; one around Staten Island (Prenski, personal communication) and one between the north eastern edge of Burdwood bank (des Clers et al, 1996) and the Falkland Islands themselves. Thus it seems quite likely that, in general, animals spawning in Falkland Island waters recruit in waters around the Islands, moving to deeper water off-shelf rather than along the shelf.…”
Section: Discussionmentioning
confidence: 99%
“…An unsuccessful attempt to assess the Falkland Islands toothfish population using a DeLury depletion method on very localised areas was made by des Clers et al (1996). At the time there were insufficient data to undertake an age-based, fishery-wide population model; a situation that has since been rectified.…”
Section: Introductionmentioning
confidence: 99%